Effect of Amaranth-Containing Dietary Intervention in Improving Hemoglobin Concentration: A Systematic Review and Meta-Analysis - Mekdes Tigistu Yilma; Aberash Eifa; Mehretu Belayneh; Alemselam Zebdewos Orsango (Public Health Reviews)
ObjectiveAmaranth, a nutritious iron source, is known for treating anemia in young children and lactating mothers, but its effectiveness in reducing hemoglobin concentration needs further investigation. Therefore, this study aimed to summarize the effectiveness of amaranth-based food interventions in improving hemoglobin concentration.MethodA randomized controlled trial and quasi-experimental study conducted since 2000 were searched in databases like PubMed, Scopus, Embase, Cochrane, AJOL, and Web of Science using prespecified keywords. Excel and Stata 17 were used for data extraction and analysis. Methodological quality was assessed using the JBI systematic review critical appraisal tool. Meta-analysis was done to estimate the overall intervention effect.ResultTen studies were included from 1,032 articles (n = 1,225). The standardized mean hemoglobin concentration difference between groups was positive, with an overall effect of 0.08 (95%CI: −0.11, 0.26; p = 0.433), where I2 is 57.1%.ConclusionThe studies’ interventions showed positive effects on hemoglobin concentration, but their effectiveness was not statistically significant. This suggests the need for research on the impact of different cooking methods on iron bioavailability, phytic iron ratio, and intervention effects across different populations.Systematic Review RegistrationIdentifier PROSPERO CRD42023476402.